Capacity building for school improvement: knowledge production and utilization - Stringer, P (Athens Institute for Education and Research, 2010)
Educational reform, focused on promoting student learning, depends on schools’ capacity to improve. Building capacity for school improvement is critical. This paper explores capacity building in one low decile, multicultural New Zealand primary school from the perspective of teacher (individual and collective) and systemic knowledge production and utilization. The research, positioned within an interpretivist paradigm, utilizes a case study and grounded theory approach to explore knowledge production and utilization that is situated, connected, involves leadership and management and is outcomes based. Knowledge production and utilization is time and context dependent and is unique to setting. It occurs in response to individual and systemic need. It is a critical factor in sustaining school capacity building. Capacity building for school improvement is defined as maintaining equilibrium while generating movement in the direction of improvement. The paper explores key attributes of knowledge production and utilization within a framework of: school vision that secures a sense of direction and purpose; school culture which provides a suitable platform for enacting performance; professional development that facilitates individual, collective and systemic learning; and school stakeholder activity that promotes knowledge acquisition, distribution, adaption and usage systems and processes. The individual, collective and systemic dimensions of knowledge production and utilization serve a predictive purpose. Predictive purpose is defined as the ability to determine future pathways for improvement based on evidential data processed, analyzed and modified to site specification. Knowledge production and utilization holds considerable promise for school improvement and, as such, requires deeper investigation.
Keywords: Capacity building; School improvement; Education; Knowledge production and utilization